Some aspects of features concept and nature of environmental safety life urban population - Kirova, M. (Land Management, Cadastre and Land Monitoring, 2017)
Proved the concept and nature of the environmental safety of life of the urban population. A structural levels in the list of objects to enter the security levels of urban or rural communities of local communities, which changes the nature of the institutional environment environmental security.In assessing the quality of life of urban society used many parameters of socio-economic and environmental. General rules on the prevention of environmental degradation and risks to human health set forth in the applicable law "On Environmental Protection", on the basis of which developed a number of legal documents.As for the capital of Ukraine - Kyiv, it is a great cultural, historical and commercial and industrial center. So we can safely say that Kyiv is characterized by all the environmental problems that are inherent in all large cities. This, above all, traffic pollution, changes in the air quality, noise pollution, emissions of chemicals into the atmosphere, pollution, toxic waste, the problem of waste. But a special place in this region occupies a radioactive problem due to the Chernobyl nuclear power plant. Also, nearby, in the Kyiv region Kiev reservoir are with not the best environmental conditions. The most important components of ecosystems: the air of the city, urban and suburban water sources, soil city. International experts conducted a study in 215 cities around the world. Kyiv international ranking is 29 in place pollution. Thus, the problem of environmental security for the population of the city. Kyiv, as many large cities in Ukraine is quite relevant.In this regard, the article studies that the environmental safety of life of the urban population in the context of national security - a state of effective security systems (environment) interconnected structural levels of the individual, the local community, society, state and international (global) community of aggregate factors that endanger or threaten the very existence of which is used in this definition of "effective protection", which is intended to emphasize that the effective nature of the safety of Mr. eredbachaye not only their comprehensive protection, but also holding on to them if necessary legitimate preventive measures to reduce the level of risk (threat). A structural levels in the list of objects to enter the security levels of urban or rural communities of local communities, which changes the nature of the institutional environment environmental security.Keywords. Safety, national security, environmental security, urban environment, urban community.